Evaluation In Vitro De L’activité Antimicrobienne Des Extraits De Cassia Alata Linn. (Fabaceae) - Pissang, Passimna; Agban, Amégninou; Hoekou, Yao Patrick; Tchacondo, Tchadjobo; Sadji, Adodo Yao; Effoe, Stéphane; Karou, Simplice Damintoti; Batawila, Komlan (European Scientific Journal, ESJ, 2016)
Cassia alata (Linn) is a Togolese flora plant traditionally used in the treatment of skin diseases and diarrhea. The objective of this work was to evaluate the in vitro antimicrobial activity and to highlight certain phytochemical total and fractionated extracts of this plant harvested in southern Togo. These extracts were obtained from polar solvents such as water, ethanol and ethanol / water mixture in equal volume. Microbial strains used consisted of bacteria, Staphylococcus aureus, Escherichia coli and Klebsiella oxytoca and yeasts, Candida albicans and Candida krusei. The antimicrobial activity was evaluated by the liquid medium dilution method coupled to spread on solid medium. Highlighting chemical groups was made by a brief qualitative phytochemical analysis from staining tests. The results show that the ethanol leaves crude extract (EBE) was the most active of all the tested microbial strains. This extract completely inhibited the growth of S. aureus (MIC = 1.25mg/ ml.); very strongly C. albicans (PI = 94.34 % ) and C. krusei (PI = 90.67% ) and strongly E. coli ( PI = 80%) and K. oxytoca (PI=79.14 %). The other extracts were active in some organisms with percentage inhibition (PI) of between 68 and 97 %. The phytochemical screening of some extracts revealed the presence of flavonoïdes, tannins and saponins. C. alata seems to contain compounds that interact to inhibit the growth of yeasts and bacteria. These results in part to justify the use of this plant in the Togolese traditional medicines.